Heuristic algorithms for configuration of the ATM-layer over optical networks - Cinkler, T. (1997 IEEE International Conference on Communications, 1997)
A general model and algorithms are presented for the optimal configuration of the ATM layer on top of mostly optical networks. The topology of the physical layer is assumed given with the predefined paths for each node-pair. The output is the size of required ATM switches, and the configuration of both, ATM and optical switches. The obtained result is optimal in the sense of reduced resource usage on ATM level, i.e., reduced electrical processing, subject to capacity and connectivity constraints. The results are derived for WDM networks and generalized for networks with optical cables where multiple fibers per cable are used (space division multiplexing). The idea of layered design is also introduced. Since the problem is discrete by nature with multiple local optima and constraints, non-deterministic constrained discrete global optimization algorithms are used. The running time and the probability of finding global optimum are compared for these algorithms.